Strategi Pengembangan Nilai Anti Kekerasan Dalam Lingkungan Pendidikan Islam - Zaidan Aimar Khadafi; Meyniar Albina (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research aims to analyze measures for preventing violence based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 82 of 2015 concerning the Prevention and Handling of Acts of Violence in Educational Institutions. In addition, this study examines efforts to build a culture of peace within Islamic educational institutions. The method employed is a literature review with data collected through documentation. The results of the study indicate that educational institutions need to develop an anti-violence attitude, formulate, and publish policies related to violence prevention. Meanwhile, local governments are responsible for establishing prevention task forces, fostering collaboration, and monitoring policy implementation. On the other hand, Islamic educational institutions play a role in creating a peaceful environment, developing Standard Operating Procedures (SOP) for prevention, and providing accessible service information, such as websites, emails, and contact numbers. Islamic educational institutions are also expected to cultivate a culture of peace through acknowledgment of mistakes, tolerance, apologies, cooperation, mutual trust, appreciation for environmental preservation, and accountability for actions taken.